Narrowband adaptive array beamformer design with broadband capability - Wang, Jin (Nanyang Technological University, 2022)
This dissertation proposes a new narrowband antenna array processing method, whose purpose is to provide spatial filtering on a specific limited bandwidth. The two parts together construct this method. In the first part, under the condition that the specified target angle and the center frequency of interest are fixed, the signal passing through the processor will have unity gain. In the second part, the method uses additional constraints to solve the problem of signal frequency offset, ensuring that the length of the processor's response curve is approximately equal to the bandwidth of the desired signal. We use Matlab to study the performance of the narrowband array processor, and the results show that the design can handle broadband signals as well with a certain bandwidth. At the same time, this method can be used as a reference when designing a broadband antenna array processor with no predetermined delay.